Effects of changes in import tariff on Nigerian palm oil industry - Egwuma, Henry (2016)
The palm oil industry has played a major role in the Nigerian economy in terms of its contribution as a source of food and an employer of labor. However, its contribution has dwindled over the years. While there has been a significant increase in domestic consumption, the production of palm oil has been rather sluggish giving rise to an increase in imports. Thus, a major policy thrust of the government in the palm oil industry is to enhance production to meet domestic demand while at the same time reducing reliance on imports and ensuring the competitiveness of the industry in the international market. As a step to protect domestic producers and stimulate production, the government in 2005 applied an import tariff of 50% which was reduced to 35% since 2008. With the help of this trade policy, local producers are shielded and local palm oil is able to compete with imported palm oil. In other words, domestic farmers are incentivized through the import substitution policy of the government which effectively raises the domestic price of palm oil relative to the world price. This policy measure, notwithstanding, domestic production has relatively remained stagnant as high costs of production make domestic palm oil production unable to compete. The main objective of this study, therefore, is to determine the effects of changes in import tariff structure on the Nigerian palm oil industry. The Nigerian palm oil market model was first developed, consisting of five behavioral equations for area harvested, yield, import demand, domestic demand and producer price of palm oil and four identity equations. Annual time series data from 1970 to 2014 was utilized and the model was estimated using the autoregressive distributed lag (ARDL) modeling technique. A number of economic and statistical criteria were used to evaluate the estimated equations. Specifically, the estimated equations were evaluated based on the size and signs of the coefficients, coefficient of multiple determination (R2), t-statistics, and diagnostic tests including a test for serial correlation, normality, misspecification, and parameter stability. Further, the performance of the model was validated using the root mean square percentage error and Theil’s inequality coefficient. The model was then used to generate baseline projections for the Nigerian palm oil industry from 2012 to 2020, a period of nine years, and to simulate the effects of changes in import tariff on the levels of supply and demand as well as prices. Four scenarios are considered including a 10%, 30%, 50%, and 100% reduction in import tariff. The results from the simulation analysis reveal that all the scenarios would result in a decline in palm oil production, an increase in imports and domestic consumption of palm oil, and a decrease in domestic and producer prices of palm oil. In addition, import tariff reductions would lead to a net welfare gain to the society attributable to the gains in consumer surplus arising from lower prices and efficient allocation of productive resources. The fall in producer prices would result in a net loss of producer welfare. Given an exchange rate of N199.05 to 1 US dollar, the results indicate that a 10% import tariff reduction yielded a net gain of N2.95 billion to the society by 2020, which can be attributed to the sufficiently large gains in consumer surplus as a result of the reductions in consumption distortions and inefficiencies in production associated with the imposition of import tariff. By 2020, the gain in Nigerian consumer surplus was estimated at N15.85 billion while the loss in producer surplus was N9.98 billion. Also, the reduction in import tariff resulted in loss in government revenue because final government revenue was less than the initial government revenue from imports. The loss in government revenue was estimated to be N2.92 billion by the end of the forecast period. The numerical values of these welfare measures increased along with the increase in the percentage reduction in import tariff. Further analysis shows that Nigerian palm oil producers can be compensated through a deficiency payment scheme as an alternative policy measure. The results indicated that when import tariff is reduced by 30% and combined with a policy of deficiency payment to producers, the output and income of palm oil producers are maintained and no additional fiscal burden is transferred to the government. Specifically, the net welfare effect of this scenario was positive and increased during the forecast period. Thus, by 2020, the net gain to the society increased by N3.89 billion. This outcome was possible because the final revenue from a 30% import tariff reductions was more than sufficient to cover the costs of deficiency payments to Nigerian palm oil producers. The findings suggest that this policy option is superior in that it allows for output, and hence income of domestic producers, to be maintained at baseline levels. In this way, domestic producers are compensated for welfare loss, consumer welfare is preserved and government budget does not suffer additional burden.